Secure protection of video recorder video in smart car - Cheonshik Kim; Dongkyoo Shin; Dongil Shin; Chin-Nung Yang (International Journal of Distributed Sensor Networks)
Many automobile drivers have come to believe that installation of video recording equipment in a car is essential to providing evidence in case of a car accident and to facilitate reporting to police. Thus, it is important to develop an in-vehicle video recorder with high resolution to document accidents. To provide such video quality, the H.264 video format, which offers high compression and good quality, has been used for an in-vehicle video recorder. However, due to problems with fabricated evidence of digital records, we propose a new watermark method to authenticate in-vehicle video. This watermarking scheme authenticates and protects in-vehicle video. The proposed scheme manipulates the quantization table of the I-frames in car surveillance videos and embeds watermarks in the I-frames. Experimental verification was done to confirm the authentication and tamper detection of the proposed watermark image method for in-vehicle video.